PERLINDUNGAN KONSUMEN MUSLIM MELALUI PENCANTUMAN SERTIFIKAT DAN LABEL HALAL PADA PRODUK PANGAN NON KEMASAN - Siti Nur Azizah (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
Law enforcement on the guarantee of halal products has not been fully realized given the enactment of UU JPH on certification obligations and the labeling of new halal products 5 years since the enactment of the law in accordance with the provisions of Article 67 paragraph (1), so that law enforcement that includes human resources factors, Law, Facilities and infrastructure, legal culture and socialization to the community are inefficient and effective. To create the benefit of products that will be consumed by Muslims especially non-packaged food products, the implementation of halal certification and labeling implemented one roof service or made into one door and strengthen the authority of the Indonesian Council of Ulama in providing protection and legal certainty to Indonesian consumers by making The Presidential Decree governing the transitional period of the MUI as an institution currently establishing halal certification to BPJPH based on Presidential Regulation No. 83 of 2015 on the Organizational Structure of the Ministry of Religious Affairs. In this case the involvement of MUI becomes an important thing in BPJPH organization. This study uses a normative juridical approach that is research that emphasizes on the use of legal norms in writing that is associated with the practice and perception made by informants. The result of the research is consumer protection in the perspective of al-maslahah not yet maximally seen from several factors as follows: Factor of law of guarantee of halal product which not yet effective, human resource factor has no technology transfer and transfer knowledge, Supporting facilities and infrastructure, Socialization needs to be done by the Government in this case the Ministry of Religious Consumer Protection should be strengthened through the transfer of technology and knowledge. Strengthening the socialization of halal product guarantee from voluntary to mandatory by government and local government to producers and consumers. Establishment of BPJPH structures in the area should be done considering that JPH must be valid throughout Indonesia. Therefore, the procurement of adequate facilities and infrastructure for halal product guarantee is required.